2013
DOI: 10.1002/joc.3648
|View full text |Cite
|
Sign up to set email alerts
|

Scenario development for estimating potential climate change impacts on crop production in the North China Plain

Abstract: ABSTRACT:It is important to investigate potential changes in temperature, precipitation and solar radiation for assessing the impacts of future climate change on agricultural production for specific regions. In this study, climate scenarios of precipitation, temperature and solar radiation for the North China Plain (NCP) were constructed in terms of stochastic daily weather sequences. A nonhomogeneous hidden Markov model (NHMM) was used to downscale daily precipitation projections at 32 stations during winter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In fact, Michel and Makowski () found wheat yields to be stagnating and declining in some European countries but increasing in others. Nevertheless, a number of studies have found that climate change has a negative effect on potential wheat yield, considering projections of the variables that influence wheat production, for example, precipitation or temperature (Bell and Fischer, ; Pathak et al ., ; Luo et al ., ; Li et al ., ; Liu et al ., , ; Lobell et al ., ; Chen et al ., ). According to our results, the increase of solar radiation over Spain could force a wheat‐yield decrease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Michel and Makowski () found wheat yields to be stagnating and declining in some European countries but increasing in others. Nevertheless, a number of studies have found that climate change has a negative effect on potential wheat yield, considering projections of the variables that influence wheat production, for example, precipitation or temperature (Bell and Fischer, ; Pathak et al ., ; Luo et al ., ; Li et al ., ; Liu et al ., , ; Lobell et al ., ; Chen et al ., ). According to our results, the increase of solar radiation over Spain could force a wheat‐yield decrease.…”
Section: Discussionmentioning
confidence: 99%
“…North China (34°–44°N, 110°–120°E) is a highly populated area and one of major agricultural, industrial and economic centres of China (Zhang et al ., 2015). Water resources are very important for agricultural security and economic development in north China, while water resources in north China are relatively scarce (Ge and Huang, 2001; Huang et al ., 2003; Chen et al ., 2013; Zhang et al ., 2014). Precipitation in north China is an important source of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…North China (35 • -44 • N, 110 • -120 • E) is a densely populated area and one of the major political, economic and agricultural centers of China (Gao et al 2022). Water resources in North China are relatively scarce, precipitation is an important source and the rainy season is very concentrated compared to other regions in China (Chen et al 2013, 2020, Ge and Huang 2001, Pei et al 2015, Chen and Sun 2019, Li and Lei 2022. Precipitation in North China is mainly concentrated in summer, so many scholars have conducted numerous studies on summer precipitation in North China (i.e.…”
Section: Introductionmentioning
confidence: 99%